Intelligent Web Data Management: Software Architectures and Emerging Technologies - Ma, Kun.; Abraham, Ajith; Yang, Bo.; Sun, Runyuan; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book presents some of the emerging techniques and technologies used to handle Web data management. Authors present novel software architectures and emerging technologies and then validate using experimental data and real world applications. The contents of this book are focused on four popular thematic categories of intelligent Web data management: cloud computing, social networking, monitoring and literature management. The Volume will be a valuable reference to researchers, students and practitioners in the field of Web data management, cloud computing, social networks using advanced intelligence tools.
Cloud Computing -- Social Networking -- Monitoring -- Literature Management.
Keywords: Computational intelligence; Artificial intelligence; Software engineering; Database management; Computational Intelligence; Artificial Intelligence; Software Engineering; Database Management